2015
DOI: 10.1037/a0036981
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the effects of a utility-value intervention to help parents motivate adolescents in mathematics and science.

Abstract: A foundation in science, technology, engineering, and mathematics (STEM) education is critical for students’ college and career advancement, but many U.S. students fail to take advanced mathematics and science classes in high school. Research has neglected the potential role of parents in enhancing students’ motivation for pursuing STEM courses. Previous research has shown that parents’ values and expectancies may be associated with student motivation, but little research has assessed the influence of parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 57 publications
4
89
0
6
Order By: Relevance
“…Harackiewicz et al (32) found that this intervention increased students' STEM course-taking in the 11th and 12th grades of high school by approximately one semester of additional STEM course-taking on average. Moreover, Rozek et al (33) showed that those effects were mediated by changes in parents' and students' attitudes about STEM topics.…”
Section: Current Studymentioning
confidence: 99%
“…Harackiewicz et al (32) found that this intervention increased students' STEM course-taking in the 11th and 12th grades of high school by approximately one semester of additional STEM course-taking on average. Moreover, Rozek et al (33) showed that those effects were mediated by changes in parents' and students' attitudes about STEM topics.…”
Section: Current Studymentioning
confidence: 99%
“…The authors found a significant difference in the level of advanced math and science coursetaking between those in the intervention and control groups, with the former taking nearly a full semester more of mathematics and science (8.31 vs. 7.50 semesters). Rozek et al (2015) also used the WSFW data to examine how parents influenced their children's math coursetaking patterns in high school. Parents were randomly assigned to one of two groups.…”
Section: Involvementmentioning
confidence: 99%
“…Latar belakang keluarga, mencakup sosial ekonomi dan tingkat pendidikan orangtua. Tingkat pendidikan orangtua memiliki pengaruh terhadap aspirasi karier remaja (Archer, DeWitt, & Wong, 2014;Correa-Velez, Gifford, McMichael, & Sampson, 2017;Rimkute, Torppa, Eklund, Nurmi, & Lyytinen, 2014;Rozek, Hyde, Svoboda, Hulleman, & Harackiewicz, 2015;Sawitri, Creed, & Zimmer-Gembeck, 2014;Vuolo, Mortimer, & Staff, 2014). Hal tersebut diduga karena keluarga yang memiliki tingkat pendidikan yang tinggi, berpandangan bahwa pendidikan merupakan hal yang signifikan bagi kehidupan anaknya dan kesuksesan karier anak ke depannya (Rimkute et al, 2014;Sawitri et al, 2014;Vuolo et al, 2014).…”
Section: Pengaruh Tingkat Pendidikan Orangtua Terhadap Aspirasi Karieunclassified